PENINGKATAN KETERAMPILAN MENYIMAK CERITA ANAK MELALUI PENDEKATAN SAVI (SOMATIS, AUDITORI, VISUAL, INTELEKTUAL) DAN MEDIA AUDIO VISUAL PADA SISWA KELAS V SD NEGERI NGADIREJO 01 KARTASURA KABUPATEN SUKOHARJO TAHUN PELAJARAN 2013/2014 - Minsih, Minsih Minsih; Maya, Dewi (Profesi Pendidikan Dasar, 2014)
This study aims to improve listening skills of childrens story telling using SAVI approach(Somatic, Auditory, Visual, Intellectual) and audio-visual media of fifth-grade studentsof Ngadirejo 01 Elementary School Kartasura, 2013/2014 school year. This type ofresearch is PTK (Classroom Action Research). This study conducted two cycles with twomeetings each cycle. The subjects of this study were fifth-grade students of Ngadirejo01 Elementary School Kartasura as many as 43 students and teachers as subject-actorsof SAVI approach and audio- visual media . The results showed an increase in students’listening skills. It can be seen from: 1) Pay attention to the story; before action 62,79%,first cycle 83.71% and second cycle 100%, 2) Identifying topics story; before actions37.20 % , cycle I 55.81 % and second cycle 80.23%, 3) Answering questions; beforeactions 41.86%, first cycle 66.27% and second cycle 80.22%, 4) Retelling the story;before actions 27.90%, the first cycle 52.32% and second cycle 80.22%. The test resultsof listening learning also increased. It can be seen from the study: before the actions39.54%, first cycle 74.41% and second cycle 100%. The conclusion of this study is theapplication of the SAVI approach (Somatic , Auditory , Visual , Intellectual) and audiovisualmedia can improve listening skills in children story telling of fifth-grade studentsof Ngadirejo 01 Elementary School Kartasura.